Multiphoton transitions for delay-zero calibration in attosecond spectroscopy. (9th January 2015) - Herrmann, J; Lucchini, M; Chen, S; Wu, M; Ludwig, A; Kasmi, L; Schafer, K J; Gallmann, L; Gaarde, M B; Keller, U
Abstract: The exact delay-zero calibration in an attosecond pump-probe experiment is important for the correct interpretation of experimental data. In attosecond transient absorption spectroscopy the determination of the delay-zero exclusively from the experimental results is not straightforward and may introduce significant errors. Here, we report the observation of quarter-laser-cycle (4 ω ) oscillations in a transient absorption experiment in helium using an attosecond pulse train overlapped with a precisely synchronized, moderately strong infrared pulse. We demonstrate how to extract and calibrate the delay-zero with the help of the highly nonlinear 4 ω signal. A comparison with the solution of the time-dependent Schrödinger equation is used to confirm the accuracy and validity of the approach. Moreover, we study the mechanisms behind the quarter-laser-cycle and the better-known half-laser-cycle oscillations as a function of experimental parameters. This investigation yields an indication of the robustness of our delay-zero calibration approach.